Zakat as a Deduction from Taxable Income (Effectiveness Study of Article 22 of Law on Zakat Management Number 23 of 2011 Banjarmasin City) - Parman Komarudin; Yati Nurhayati; Muhammad Hendri Yanova; David Fuad Habibie; Khairul Anam (Faculty of Law, Universitas Pekalongan, 2022)
This study aims to analyze Article 22 of Law on Zakat Management Number 23 of 2011, in which zakat paid to agencies/institutions authorized by the government can be deducted from taxable income in the city of Banjarmasin. The research method used is the sociology of law (socio-legal research) using an interdisciplinary approach between normative research aspects and a sociological approach that uses qualitative analysis. The result of the research is that in the practice of zakat as a deduction from taxable income, of course, zakat must be paid to an official body or institution that the government has approved. On this basis, the payment of zakat made by the taxpayer must be made to the agency or institution. Effectiveness of Article 22 of Law on Zakat Management Number 23 of 2011 concerning Zakat Management, there are several factors that do not affect and there are also several factors that do. There are 3 factors that do not affect the effectiveness of the regulation, namely the rule of law factor, the law enforcement factor, and the facility or facility factor. While the factors that affect the effectiveness of these regulations are community factors and cultural factors.